Pengembangan Buku Company Profile Sebagai Media Pengenalan Jurusan Teknik Informatika dan Komputer Fakutas Teknik Universitas Negeri Makassar - Renaldy Junedy; Muh. Yusuf Mappeasse; Mustari S. Lamada (Jurnal Pendidikan Terapan, 2025)
This study aims to determine the results of testing, effectiveness, and application of company profile book development as an introduction media for the Department of Informatics and Computer Engineering, Faculty of Engineering, Makassar State University. This research is a Research and Development (R&D) development using a 4-D model (define, design, develop, disseminate). Data collection instruments used questionnaires and validation test sheets. The data analysis technique used in this research is quantitative descriptive analysis in the form of percentages. The results showed that the development of a company profile book as an introduction media for the Department of Informatics and Computer Engineering, Faculty of Engineering, Makassar State University, obtained a score of 89% in the very practical category from user responses as well as validation tests for material experts and media experts, both included in the feasible category with a score of 1. using the Guttman scale. The Company Profile book was declared effective because in terms of the results of applying the book to students it achieved 96% completeness in the very good category so that it was declared effective. Based on these data it can be concluded that the development of a company profile book as an introduction medium for the Department of Informatics and Computer Engineering, Faculty of Engineering, Makassar State University was accepted and used as an introduction medium for agencies to the general public.